Antibiotic sensitivities of Streptococcus pneumoniae, viridans streptococci, and group A hemolytic streptococci isolated from the maxillary and ethmoid sinuses. - Keleş, Erol; Aral, Murat; Alpay, H Cengiz (My University, 2006)
OBJECTIVES: To investigate antibiotic sensitivities of Streptococcus pneumoniae, viridans streptococci, and group A hemolytic streptococci isolated from the culture materials obtained from the sinuses of patients undergoing functional endoscopic sinus surgery due to chronic sinusitis. PATIENTS AND METHODS: We recruited 93 patients (63 males, 30 females; mean age 36+/-17.5; range 19 to 68 years) who underwent functional endoscopic sinus surgery due to chronic sinusitis. Before surgical intervention, in order to eliminate a possible contamination from the skin and neighboring structures, nasal mucosa was cleansed with povidone-iodine solution. Nasal smear samples were obtained from all the patients before and after applying povidone-iodine solution. Streptococcus pneumoniae, viridans streptococci and group A hemolytic streptococci that were isolated from the cultures were tested for antibiotic sensitivity. RESULTS: The number of anaerobic bacteria isolated from 58 patients (62.3%) before applying povidone-iodine was 72, following the application of povidone-iodine a total of 16 microorganisms were identified from 12 patients (12.9%). Microorganisms were isolated from 95.6% (89/93) of the samples obtained from the maxillary sinuses and 91.3% (85/93) of the samples obtained from the ethmoid sinuses. The most commonly identified microorganisms from both sinuses were coagulase negative staphylococcus followed by viridans streptococci, coagulase positive staphylococcus, Streptococcus pneumoniae and group A hemolytic streptococci. For viridans streptococcal strains that were isolated, 33.3% were resistant to tetracycline, 23.8% to chloramphenicol, and 19.04% to penicillin. Hemolytic streptococci strains were sensitive to penicillin, ofloxacin, ceftriaxone, and cefepime in all the groups; however, they had 50% resistance to erythromycin and chloramphenicol and 100% resistance to tetracycline. The resistance pattern of the isolated Streptococcus pneumoniae strains were as follows: 25% to penicillin, 66.6% to trimethoprim/sulfamethoxazole, 41.6% to erythromycin, 58.3% to tetracycline, 33.3% to chloramphenicol and 16.6% to rifampin. All of the isolated strains were sensitive to vancomycin. CONCLUSION: We suggest that identification of strains that are resistant to penicillin and other antibiotics is an important tool for choosing empirical treatment for Streptococcus pneumoniae, viridans streptococci, and group A hemolytic streptococci in clinical practice. Viridans streptococci which are frequently isolated from chronic sinusitis patients should be kept in mind.
Keywords: Adult; Aged; Anti-Bacterial Agents; Chronic Disease; Drug Resistance, Bacterial; Ethmoid Sinus; Female; Humans; Male; Maxillary Sinus; Microbial Sensitivity Tests; Middle Aged; Sinusitis; Streptococcus; Streptococcus pneumoniae; Viridans Streptococci; antiinfective agent; adult; aged; alpha hemolytic Streptococcus; antibiotic resistance; article; chronic disease; classification; drug effect; ethmoid sinus; female; human; male; maxillary sinus; microbiological examination; microbiology; middle aged; pathology; sinusitis; Streptococcus; Streptococcus pneumoniae